P67 Moving into year 7: A pilot study to assess to the usefulness of an on-line group session to prepare young people with cystic fibrosis for transitioning to secondary school. (11th November 2022) - Beech, G; Lawrence, C; Walsh, A; Fogg, H; Woodland, C; Thursfield, RM
Abstract : Introduction: Starting secondary school is a big step for any child and their family but particularly so if they have a chronic condition such as cystic fibrosis (CF). Hospital teams can assist with the preparation required for the transition. CF is different from other chronic conditions with respect to holding transition events, as face to face events are not possible due to the risk of cross-infection of different organisms between patients. In order to overcome this, the CF team at Alder Hey Children's Hospital created a virtual event named 'MI7' (Moving Into year 7). Method: Events were held via video conferencing software and questionnaires sent to all participants before the event and afterwards. All patients in year 6 cared for by the Alder Hey CF network were invited to participate with a maximum of 7 young people per group. Packs were sent out beforehand. Sessions consisted of ice-breaker games and CF team led discissions. Results: A pilot event was held in 2019. This was well-received and follow-up from the families was sought after the first term at secondary school. Unfortunately, due to the COVID pandemic, the event could not be held in 2020, but it went ahead in 2021 and 2022. There was a distinct difference between the event held in 2019 and 2021/22, in that everyone (the hospital team members, and the patients and their families) was much more familiar with participating in a virtual event, due to the way this practice had become commonplace during the COVID pandemic. Overall 22 people have participated in these events to date. 25% described being worried about going to secondary school. All young people gave at least one thing that they were worried about and the most common finding was getting lost (21%). The most common CF related worry was regarding taking creon and 12% cited this as a concern. Less than 25% of all concerns given related to CF with the remainder being more generic concerns. All participants stated that they enjoyed the event and most found it useful. Conclusion: Transition events to help this patient population move from primary to secondary school are feasible, enjoyable for young people with CF and useful.